Compact Low-Cost Reconfigurable Microwave Bandpass Filter Using Stub-Loaded Multiple Mode Resonator for WiMAX, 5G and WLAN Applications - Hasan, Yousif Mohsin; Abdullah, Abdulkareem Swadi; Alnahwi, Falih Mahdi (Basrah Journal for Engineering Sciences, 2022)
This paper presents a compact, low-cost reconfigurable bandpass filter (BPF) for WiMax, 5G, and WLAN applications. The BPF consists of a half-wavelength resonator folded as C-shaped by a pair of symmetrical PIN diodes and a central quarter-wavelength resonator to form an E- shaped stub-loaded multiple-mode resonator (SL-MMR). The feed line is made of two subsections separated by a gap which acts as a fixed capacitance and allows the filter to have bandpass behavior. The proposed filter is modeled using the even and odd mode analysis to predict the locations of the resonant frequencies. The simulation results show that the filter covers the frequency range (3.38-3.95) GHz with a center frequency of 3.52 GHz at the ON state of a pair of PIN diodes. On the other hand, the BPF covers the frequency range (4.7-5.93) GHz with a center frequency of 5.2 GHz, at the OFF state of the diodes. The results also show a small insertion loss at the filter passband with two sharp transmission zeros at the stopband.